The Berenstain bears and too much pressure - Berenstain, Stan, 1923-2005 (Berenstain, Stan, 1923-2005. First time books., 1992)
Members of the Bear family commit themselves to so many time-consuming activities that the resulting stress brings on a crisis and makes them admit that there are only so many hours in a day.